2003
DOI: 10.1164/rccm.200209-985bc
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Preoperative Assessment in Predicting Pulmonary Risk after Nonthoracic Surgery

Abstract: We examined the accuracy of preoperative assessment in predicting postoperative pulmonary risk in a prospective cohort of 272 consecutive patients referred for evaluation before nonthoracic surgery. Outcomes were assessed by an independent investigator who was blinded to the preoperative data. There were 22 (8%) postoperative pulmonary complications. Statistically significant predictors of pulmonary complications (all p < or = 0.005) were as follows: hypercapnea of 45 mm Hg or more (odds ratio, 61.0), a FVC of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
18

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 13 publications
3
75
0
18
Order By: Relevance
“…Cigarette smoking is a risk factor for PPCs, even in the absence of chronic lung disease or adjusting for other co-morbidities commonly seen in smokers [31, 32]. Current smoker has an additional risk, and there is a correlation between the cumulative amount of smoking and the risk of PPCs [33].…”
Section: Risk Factors For Ppcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cigarette smoking is a risk factor for PPCs, even in the absence of chronic lung disease or adjusting for other co-morbidities commonly seen in smokers [31, 32]. Current smoker has an additional risk, and there is a correlation between the cumulative amount of smoking and the risk of PPCs [33].…”
Section: Risk Factors For Ppcsmentioning
confidence: 99%
“…The presence of COPD increases the risk of PPCs by one- to twofold [20, 32, 46]. The increased risk in COPD patients attributes to the airflow obstruction and the presence of other co-morbidities commonly seen in smokers, such as CHF and weight loss.…”
Section: Risk Factors For Ppcsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,48,49 For example, in a recent study 48 significant multivariate predictors of pulmonary complications after non-thoracic surgery were age > 65 yr, and a smoking history of more than 40 yr. Pedersen et al 50 found that risk factors for perioperative pulmonary complications included patient age older than 70 yr, chronic obstructive lung disease, major surgery, and the use of muscle relaxants during anesthesia. A recent literature review confirmed that advanced age is a risk factor for postoperative pulmonary complications, even after adjustment for other comorbid conditions.…”
Section: Agementioning
confidence: 99%
“…In general, the incidence of postoperative complications (POPCs) was determined to be higher in cases at and over the age of 65 years [4,5].…”
Section: ) Agementioning
confidence: 99%